Dexamethasone Intravitreal Implant for Diabetic Macular Edema: Indications for a PRN Regimen of Treatment. Issue 4 (July 2015) - Panozzo, Giacomo; Gusson, Elena; Panozzo, Giorgio; Mura, Giulia Dalla
Purpose: To define the mean time of first recurrence of diabetic macular edema (DME) after a single injection of dexamethasone intravitreal implant (DEX-I), reducing the burden of monthly visits during a PRN regimen of treatment. Methods: Twenty phakic eyes with DME (12 eyes naïve and 8 eyes with edema persistent after previous treatments) were followed monthly after DEX-I injection until evidence of first recurrence of edema, defined as a change in visual acuity (VA) ≥5 letters and/or in foveal thickness (FT) ≥50 µm. Reaching this point, the eyes were re-treated. Monitored parameters were changes in VA, FT, intraocular pressure (IOP), and lens opacity. Results: Maximal efficacy was registered at month 1, when mean VA improved by 14 letters (19%), FT decreased by 325 µm (43.7%), and in 15 eyes (75%) edema was completely reabsorbed. The mean time of first recurrence was 5.1 months. No statistical difference was found between eyes with naïve or persistent DME. Five eyes needed topical medication for modest temporary IOP increase (21-24 mm Hg) between months 2 and 4. No increase in lens opacities was registered during follow-up. Conclusions: According to the results of this study, the first signs of DME recurrence after DEX-I injection appear at a mean time of 5 months, suggesting that an appropriate and prudent time schedule for a PRN regimen could be limited to monthly tonometry and a first complete examination not before 4 months.